Occupant Safety and Risks Related to Building Envelope - Ustaoglu, Semih Serkan; Limoncu, Sevgul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
The need for shelter in humans has emerged to protect themselves from adverse environmental conditions and to meet I their physiological needs in a safe and healthy living area. However, in today's spatial changes and transformations, a wide range of risk-based problems of the occupants are either ignored /pushed in to the background in the design processes, or people are afraid of such problems. In built environments, designed by ignoring these risks, people constantly feel threatened and endangered. People's lives are hampered by the problems posed by these risks that must be prevented before they occur. However, in Turkey, there exists no architectural design procedure that considers the risks in building production. This is mainly because occupants and builders prioritize economic and social concerns rather than health and safety issues. Arising from the need to live in a safe environment, buildings have turned into an element that negatively affects the need of people due to the changes in time. Building envelopes play an important role in providing a safe environment to protect buildings from external safety issues, especially as a boundary between indoor and outdoor environments. However, as the changes over time has been reflected in the building envelope, there have been significant increases in the downside of the occupant safety-building envelope relationship. The study aims to classify safety risks of the building envelope according to incidents faced by occupants, to define circumstances to be considered in design processes and, to contribute to the design process with the proposal of a risk analysis method. The study is limited to the risks of the building and the nearby surroundings, which adversely affect the occupant safety associated with the building envelope. Risks for occupants arising from the building envelope, problems encountered, and solutions to prevent these before they occur are discussed. Risks associated with building envelopes were identified, classified, and defined through extensive literature, incident and statistical research. A risk analysis design method proposal was developed and linked with the building envelope to eliminate or resolve identified risks. Safety-related rules in architectural design are usually defined through codes and standards. However, there are different risks beyond the minimum situations likely to be encountered by occupants. Their safety levels cannot be determined by strict criteria. Each design has its own conditions; acceptable risk levels should be defined by consensus among occupants and designers. A design process, that ignores occupant safety issues, may result in injuries, damage to internal organs and skeletal system, cracks and fractures, burning, scalding, poisoning, and death. Occupants face the same life threats as building envelopes are built with similar design negligence. As a result, occupants' lives are blocked or ended. Therefore, such negative issues should be addressed as a design problem in the design process and resolved in advance. To produce solutions, building envelope, occupant, function and design risks should be identified. In the study, the common conditions of these risks were identified and examined and, consequently, physical, sociological, psychological risks based on the occupants and the problems that may occur due to the reasons of the related risks were explained in relation to the function. After the identification process, the necessary design method proposal was developed to prevent these problems in the design phase. In Turkey, design method based on risk analysis rather than the traditional approach in ensuring occupant safety should be used. Thus, a healthier and more controlled design process will be implemented and as a result, a system that prioritizes occupant safety will be established. Resolving and detailing conditions that pose a threat to occupant in the building envelope before they occur will reduce the obligations and errors in the production process, and will reduce vital safety issues even if they cannot be completely eliminated during use. This change is considered to have a positive effect on building and envelope design in Turkey, which currently carries multiple potential risks. The study is significant in defining risks arising from the building and its nearby surroundings on the basis of building envelope, revealing the adverse effects of the identified risks on the occupant, and it is thought that it will contribute to safe building design studies in the future with the proposed design method involving risk analysis which is suitable for conditions in Turkey, help to resolve risks in the design process before they occur. In addition, it is thought that the study will raise the safety awareness of occupant and designers in buildings and the nearby surrounding area.
Keywords: Building envelope; occupant risks; occupant safety; risk-analyze in methods; DESIGN; Architecture